Carbon Monoxide Fixed Point Continuous Monitor - Objective (The National Institute for Occupational Safety and Health (NIOSH), 1981)
Provide an instrument for continuous remote monitoring of carbon monoxide concentration in underground mines. Approach A carbon monoxide fixed? point continuous monitor consists of two modules. A line-powered control module is designed to power a remote transducer module; provide continuous readouts, visual and audible alarms, operational checks; and activate fans and equipment shutdown circuits if preset CO concentration levels are exceeded. How It Works The control module must be used in conjunction with a single transducer module. Developed under contract. the control module is a wall-mounted Instrument which contains a readout and alarm capability and power supply